SNP polymorphism rs80867243, rs81379421 and rs81236069 in pigs of maternal breeds - L. V. Getmantseva (Аграрная наука Евро-Северо-Востока, 2018)
Genome-Wide Association Studies (GWAS) are increasingly used in the investigation of the genetic architecture of the reproductive traits of pigs. Based on the results of these studies, 47 SNPs associated with the Total number born alive (NBA) of European breeds (Large White, Yorkshire, Landrace) were identified, which are presented in the PigQTLdb. The aim of this work is to develop a procedure for testing SNPs rs80867243 (SSC5), rs81379421 (SSC3), rs81236069 (SSC10) by PCR-RFLP and to evaluate their polymorphism in maternal pigs bred in the conditions of the Russian breeding industry. The research was carried out in pigs of Large White breed (n = 60) and Landrace (n = 63). SNP positions were determined from the last assembly of the pig genome (Sus scrofa 11.1) in the Ensembl database. The primers and restriction endonucleases for identification of SNP by PCR-RFLP were selected using Primer-BLAST and NEBcutter V2.0 programs, respectively. According to the results of molecular genetic studies, Landrace pigs are polymorphic in all investigated SNPs. The allele frequencies A and G for SNPs rs80867243, rs81379421 and rs81236069 were 0.81 and 0.19; 0.43 and 0.57; 0.21 and 0.79, respectively. In Large White pigs polymorphism was established for SNPs rs81379421 and rs81236069, the frequencies of alleles A and G were 0.07 and 0.93; 0.30 and 0.70, respectively. The methods of testing SNPs rs80867243, rs81379421 and rs81236069, which can be used in further studies on the pigs bred in breeding farms of the Russian Federation as well as in the study of associative connections of SNPs with reproductive traits are presented in the article.